The Controversy of Unregistered Marriage Trends from the Perspective of Maqa’sid Mukhallaf: Preventing Underage Marriage in Wajo Regency - Sapriadi Sapriadi; Hannani Hannani; Fikri Fikri (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
This study investigates the phenomenon of unregistered marriage and efforts to prevent underage marriage in Wajo Regency. The research aims to examine the motivations behind unregistered underage marriages through the lens of Maq??id Mukallaf and evaluate the effectiveness of local legal interventions. Wajo Regent Regulation No. 64 of 2022 serves as a key policy instrument aimed at curbing underage marriage and promoting legally recognized unions. Using a qualitative juridical approach, data were collected through in-depth interviews with marriage officials, parents, community leaders, and underage couples, supported by observation and document analysis. The study integrates Maq??id Mukallaf theory to assess the legality and ethical validity of marriage motives, alongside Ibn Qayyim al-Jawziyyah’s theory of legal change and Weber’s bureaucratic management theory to evaluate policy responsiveness and implementation. Findings indicate that although unregistered marriages involving underage couples may fulfill internal aspects such as personal capability and social support from parents and family, they are often driven by defensive motives such as avoiding complex legal procedures or social stigma which ultimately fail to meet the criteria of valid Maq??id Mukallaf. Such acts are legally and morally untenable when they cause harm to others, particularly to children. This study highlights the importance of aligning legal frameworks with religious principles and community engagement to protect children’s rights and foster sustainable social change.